Enrichment specificity of micro and nano‐sized titanium and zirconium dioxides particles in phosphopeptide mapping. (6th November 2013) - Vilasi, Annalisa; Fiume, Immacolata; Pace, Paolo; Rossi, Mosè; Pocsfalvi, Gabriella
<x xml:space="preserve">Abstract</x> Owning to their anion‐exchange properties, titanium and zirconium dioxides are widely used in phosphopeptide enrichment and purification protocols. The physical and chemical characteristics of the particles can significantly influence the loading capacity, the capture efficiency and phosphopeptide specificity and thus the outcome of the analyses. Although there are a number of protocols and commercial kits available for phosphopeptide purification, little data are found in the literature on the choice of the enrichment media. Here, we studied the influence of particle size on the affinity capture of phosphopeptides by TiO2 and ZrO2. Bovine milk casein derived phosphopeptides were enriched by micro and nanoparticles using a single‐tube in‐solution protocol at different peptide‐to‐beads ratio ranging from 1 : 1 to 1 : 200. Unsupervised hierarchical cluster analysis based on the whole set of Matrix Assisted Laser Desorption/Ionization time‐of‐flight mass spectra of the phosphopeptide enriched samples revealed 62 clustered peptide peaks and shows that nanoparticles have considerably higher enrichment capacity than bulk microparticles. Moreover, ZrO2 particles have higher enrichment capacity than TiO2. The selectivity and specificity of the enrichment was studied by monitoring the ion abundances of monophosphorylated, multiphosphorylated and non‐phosphorylated casein‐derived peptide peaks at different peptide‐to‐beads ratios. Comparison of the resulting plots enabled the determination of the optimal peptide‐to‐beads ratios for the different beads studied and showed that nano‐TiO2 have higher selectivity for phosphopeptides than nano‐ZrO2 particles. Copyright © 2013 John Wiley & Sons, Ltd.